Gestar autonomia na preparação para o parto : grupo como estratégia da abordagem centrada na gestante - Abreu, Cíntia Souza de (2019)
Childbirth, throughout history, has undergone considerable changes: it has moved from the perspective of an intimate, private and family event, to the institutionalization and technical improvement of medical and interventional practices. The resumption of the role of women in childbirth, in this context, is one of the fundamental premises of their humanization, since the aspects highlighted by public policies position women at the center of this process. Therefore, this study was conducted to investigate the insertion of Psychology in a multiprofessional team with a group of pregnant women, in preparation for childbirth, to discuss their possible contributions to this theme. This is an experiential study of a qualitative nature, characterized as research of the lived, understood as a phenomenological psychological study. In these types of studies, priority is given to the researcher's subjective plunge, beyond the intellectual way, therefore, the experience of intersubjective relations between researcher and pregnant women was privileged. The participants of this study were 12 women assisted by two Basic Health Units (SUS), and the collection of narratives via group. The group space was provided by the My Childbirth Program, a partnership between the Graduate Program in Nursing and the Graduate Program in Psychology at UFMT, which in all held 15 meetings. The comprehension of the narratives happened through the search of the meaning of the lived for the pregnant women. Lived here corresponds to the first, immediate feeling of pregnant women facing the experience. In this study, childbirth presented itself as an event permeated by feelings, different senses for each woman, however, something common to all participants was to witness the unique experience of each woman. The experiences around the practices of care and prenatal care, childbirth and birth were accentuated in the experience of interpersonal relationships established between pregnant women and the team. The support network proved to be significant for some pregnant women, however, there are other crossings that run through pregnancy and support network, such as economic issues. The group's proposal made possible the experience of exchange of experience. The attention and psychological care experienced contributed to the autonomy and safety of some pregnant women. Considering the reality and the context of public health in which this research was conducted, as well as the rates of surgical delivery performed annually in the city of Cuiabá-MT and in Brazil, as well as the crossing of relationships in the context of parturition, it was found that the group focused on pregnant women, potentiated the discussion about the humanization of childbirth and birth, which enables the confrontation of inadequate care for women. It was noted that the performance of Psychology in the contours of the ACP (Person Centered Approach), is compatible with the principles of SUS, with light technologies of childbirth and recommendations of the World Health Organization (WHO), through the belief in The tendency to update, and the attitudes of Unconditional Positive Consideration, Empathic Understanding and Congruence, proved to be contributory to facilitating the autonomy and resuming the role of women in childbirth.